PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MODEL ACTIVE LEARNING DI KELAS IX.1 SMPN 1 KECAMATAN GUGUAK - Ashri Rahmatika Firdaus; Zulfani Sesmiarni; Rodi Rodi; Yeni Fitri (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This Classroom Action Research aims to improve the learning outcomes of Islamic Religious Education through the application of active learning models to students of class IX.1 at SMPN 1 Guguak District. The learning outcomes of most students in the PAI subject show low results or are below the minimum competency standards. This is due to the low level of student involvement in the learning process, as well as the dominance of lecture methods that are less interesting for students' learning interests. This study uses a PTK design that is implemented in four cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were 32 students of class IX.1 SMPN 1 Guguak District. The data collected included the results of observations of learning activities and the results of the initial and final assessments. The results showed that the application of the active learning model can improve the learning outcomes of class IX.1 students of SMPN 1 Guguak District. In cycle I, the average student score increased compared to the Pre-Cycle, which was around 75% of students achieved minimum completeness. In cycle II, the increase in student learning outcomes was around 81.25%. In cycle III, the increase in student learning outcomes was around 87.5%. In addition, the observation results showed that students were more motivated and actively involved in the learning process using the active learning model. Thus, it can be concluded that the active learning model is effective in improving the learning outcomes of Islamic Religious Education in class IX.1 students at SMPN 1 Guguak District.